Strategic Semiconductor Leadership: Ensuring America's Economic and Defense Resilience in the 21st Century - Ghosh, Robin; Khamari, Chandi Prasad (Journal of Global Economy, Business and Finance, 2025)
The semiconductor industry has contributed to the economic stability and national defense of the United States for decades. Growing competition, particularly in Asia, places the dilemma on how the U.S. will regain its lead in semiconductor manufacturing to remain economically secure and militarily ready. If these areas are given needed attention, then it is apparent that the U.S. can safeguard its economic future and hold its technological superiority in defense. The paper concludes with a call to action for policymakers and industry leaders, featuring detailed policy recommendations requiring immediate coordinated action. This research paper examines the critical role of the semiconductor industry in maintaining the United States economic stability and national defense. In light of increasing global competition, particularly from Asia, the U.S. faces significant challenges in regaining its leadership in semiconductor manufacturing. This paper explores the intricate relationship between semiconductor dominance and national security, emphasizing the economic and defense implications. Through a detailed analysis of supply chain vulnerabilities, technological competition, and strategic initiatives, the paper presents actionable recommendations for strengthening U.S. semiconductor leadership. The findings underscore the urgent need for coordinated publicprivate partnerships, increased RD funding, and robust legislative support to secure the nations technological and economic future.